If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -76 = 6(2x + -2) + -8(-4x + -3) Reorder the terms: -76 = 6(-2 + 2x) + -8(-4x + -3) -76 = (-2 * 6 + 2x * 6) + -8(-4x + -3) -76 = (-12 + 12x) + -8(-4x + -3) Reorder the terms: -76 = -12 + 12x + -8(-3 + -4x) -76 = -12 + 12x + (-3 * -8 + -4x * -8) -76 = -12 + 12x + (24 + 32x) Reorder the terms: -76 = -12 + 24 + 12x + 32x Combine like terms: -12 + 24 = 12 -76 = 12 + 12x + 32x Combine like terms: 12x + 32x = 44x -76 = 12 + 44x Solving -76 = 12 + 44x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-44x' to each side of the equation. -76 + -44x = 12 + 44x + -44x Combine like terms: 44x + -44x = 0 -76 + -44x = 12 + 0 -76 + -44x = 12 Add '76' to each side of the equation. -76 + 76 + -44x = 12 + 76 Combine like terms: -76 + 76 = 0 0 + -44x = 12 + 76 -44x = 12 + 76 Combine like terms: 12 + 76 = 88 -44x = 88 Divide each side by '-44'. x = -2 Simplifying x = -2
| 20w^13+16w^8=w | | =x+30 | | 4(5a+2)= | | =w | | 3x^3+x^2-24=0 | | 15y+6=21 | | (-1.04)(-0.6)= | | -2(7b-7)=5-5b | | -3b-12=15 | | 5(4+k)+2(8-7k)=-36 | | W-4(w+5)=-8 | | 13-11x=8*8+16 | | 21x=267 | | 2(10x+7)-x=-157 | | 5t^2+9t-19=0 | | (4x+2)-(5x+1)= | | 20-12i=5x+(4y)i | | 21x^2-7x=0 | | 3(k+3)=k-1 | | .8x^2-4x=0 | | 5y^2+50y=0 | | 0=5x^2-15x+20 | | -29+6x=-7+3(2x-7) | | 5=(-8)-t | | 6-k=14 | | -7a=-129-65 | | -11=n-2 | | 5x+4(-x+9)=41 | | h+6=13 | | 16x+6=-11 | | y=-.50*1-2 | | y=-.50*4-2 |